High‐mobility group box 1 released by traumatic occlusion accelerates bone resorption in the root furcation area in mice. (27th November 2020) - Oyama, Mika; Ukai, Takashi; Yamashita, Yasunori; Yoshimura, Atsutoshi
Abstract: Background and objective: Traumatic occlusion can cause bone resorption without bacterial infection. Although bone resorption in periodontitis has been relatively well studied, little is known about bone resorption by traumatic occlusion. High‐mobility group box 1 (HMGB1) is released from damaged tissue and has been recently shown to promote bone resorption in a murine periodontitis model and may also promote bone resorption by traumatic occlusion. The present study aimed to examine whether HMGB1 accelerates bone resorption by traumatic occlusion in mice. Materials and methods: Occlusal trauma was induced in the lower left first molar of mice by bonding a wire to the upper left first molar, and bone resorption and osteoclast formation were evaluated histochemically. The expression of HMGB1, Toll‐like receptor 4 (TLR4; the receptor for HMGB1), and receptor activator of NFκB ligand (RANKL; an essential osteoclast differentiation factor) was evaluated immunohistologically. In addition, mice were administrated with an anti‐HMGB1‐neutralizing antibody to analyze the role of HMGB1. Results: Bone resorption and osteoclast formation gradually increased until day 5 at the furcation area after the application of traumatic occlusion. Expression of HMGB1 was observed at the furcation area on day 1, but was attenuated by day 3. Expression of RANKL gradually increased until day 3, but was attenuated by day 5. Administration of anti‐HMGB1 antibody significantly reduced the number of osteoclasts and the expression of RANKL and TLR4 at the furcation area. Conclusion: Release of HMGB1 in the root furcation area accelerated bone resorption by up‐regulating RANKL and TLR4 expression in mice with traumatic occlusion.